Pre-Operative Medications as a Predictor for Post-Operative Complications Following Geriatric Hip Fracture Surgery. (2nd April 2022) - McDonald, Christopher L.; Cohen, Brian H.; Medina Pérez, Giancarlo; Modest, Jacob M.; Kuris, Eren O.; Born, Christopher
Background: Fragility hip fractures are a common orthopedic injury seen in Emergency Departments, with variable outcomes that can range from average to devastating. Currently, few reliable metrics to predict which patients will suffer post-operative complications exist. The aim of this study was to determine if the number and type of pre-operative medications can help predict post-operative complications. Methods: A prospectively collected database of hip fracture patients was retrospectively reviewed. Patients with isolated greater trochanteric fractures, periprosthetic fractures, or re-fractures were excluded. Pre-operative baseline characteristics as well as number and type of post-operative complications were reviewed. Any complication within 6 months of surgery and complications that could be directly attributable to the surgical procedure within 2 years of surgery were examined. Major complications (return to the operating room, deep infection, pulmonary, cardiac, and hematologic) and minor medical complications were assessed. A multivariate regression model was performed to identify independent risk factors. Results: Three-hundred ninety-one patients were included. A majority were aged 80–90 and female, and lived at home prior to presentation. Overall, 33.7% of patients suffered a complication within a 2-year follow-up period. Mortality rates were 5.4%, 10.0%, and 14.9% over 30 days, 1 year, and 2 years, respectively. After assessing this relationship while controlling for age, sex, injury type, pre-operative residence, ambulatory status, ASA score, and CCI score, the relationship remained significant for both an increased number of complications ( P = .048) and a higher likelihood of having a complication ( P = .008). Cardiovascular ( P = .003), pulmonary ( P = .001), gout ( P = .002), or diabetes ( P = .042) medications were associated with a higher likelihood for experiencing a complication. Conclusions: Our study suggests that there is a strong and linear relationship between the number and type of pre-operative medications taken and risk of post-operative complications. This exists for up to 8 medications, at which point further increase does not contribute to an increased risk of complication. This relationship exists even after controlling for confounding variables and can be used by surgeons to better counsel patients and families regarding their specific risk for suffering perioperative complications.